Electron Emission from Electron-irradiated Dielectrics - Gross, Bernhard (1991)
The paper discusses methods for the measurement of the electron emission currents and the secondary electron yield for electron-irradiated dielectrics. Here the surface of the irradiated dielectric acts as both a collector and a measuring electrode, while a separate collector for recording the emitted electrons is discarded. Secondary yields for a series of dielectrics are represented in the form of a ‘universal’ curve. © 1991 IEEE